HMTP: Multipath transport protocol for multihoming wireless erasure networks. Issue 8 (5th March 2014) - Hwang, Younghak; Saha, Abhijit; Choi, Hanbit; Lim, Hyuk; Obele, Brownson O.
Abstract This paper proposes a fountain‐code‐based multipath transport protocol, called heterogeneous multipath transport protocol (HMTP), and evaluates its performance. HMTP improves the throughput performance and path utilisation of multihoming wireless erasure networks. It solves the receive buffer blocking problem and eliminates the need for retransmissions and in‐order packet delivery, both of which severely degrade the performance of existing multipath transport protocols in multihoming networks. The encoding and decoding algorithms of HMTP are based on efficient and computationally inexpensive coding algorithms such as LT codes. To minimise the fountain encoding/decoding overhead, complexity and computational cost while ensuring the desired decoding performance, the appropriate values of the parameters of the LT codes are determined. We implement and extensively evaluate the performance of HMTP using both NS‐2 simulator and an 802.11 wireless local area network laboratory test bed. Our simulations and experimental results show that HMTP significantly outperforms the concurrent multipath transfer stream control transmission protocol, especially in multihoming 802.11 wireless local area networks. Copyright © 2014 John Wiley & Sons, Ltd.